A PROPOSAL TO DEVELOP THE USE OF INFORMATION AND COMMUNICATIONS TECHNOLOGY IN AGRICULTURAL EXTENSION - Al-Jilawi, H. M. H.; Al-Mashhadani, M. A. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research  was aimed to develop a proposed vision to develop the effectiveness of the use of information and communications technology in agricultural extension work/Iraq, To achieve the research goal, the questionnaire was prepared as a tool for collecting information and included 109 items distributed over 8 axes, which are (formulating a strategic plan, providing infrastructure, disseminating culture, Security and safety of information extension, developing workers’ capabilities, improving cooperation and coordination between the extension organization and relevant authorities, Improving the target population’s access to information and extension knowledge, monitoring and evaluation. The research included the governorates of Iraq, except for the Kurdistan region, which number 15 governorates. A 50% random sample was drawn, with 8 governorates: Baghdad, Kirkuk, Babylon, Basra, Anbar, Dhi Qar, Najaf, and Karbala), and the research community included those working in agricultural extension, numbering 773 respondents. A proportional, stratified random sample was drawn with a proportion of 33.1% of the research community and 256 respondents. The data was collected, tabulated, and analyzed using statistical methods and the SPSS program to extract The results: It was concluded that all the paragraphs and axes of the proposed vision, in terms of importance and the opinions of the respondents, obtained weighted means higher than the hypothesized mean of 3 degrees, The researcher recommends the need for officials and specialists in the Ministry of Agriculture, the Agricultural Extension and Training Department, and the Agriculture Directorates to adopt the proposed vision to develop the effectiveness of agricultural extension and its use of information and communications technology.